Measurement of the top quark mass using proton-proton data at root(s)=7 and 8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2016)
A new set of measurements of the top quark mass are presented, based on the proton-proton data recorded by the CMS experiment at the LHC at root s = 8 TeV corresponding to a luminosity of 19.7 fb(-1). The top quark mass is measured using the lepton + jets, all-jets and dilepton decay channels, giving values of 172.35 +/- 0.16(stat) +/- 0.48(syst) GeV, 172.32 +/- 0.25(stat) +/- 0.59(syst) GeV, and 172.82 +/- 0.19(stat) +/- 1.22(syst) GeV, respectively. When combined with the published CMS results at s = 7 TeV, they provide a top quark mass measurement of 172.44 +/- 0.13(stat) +/- 0.47(syst) GeV. The top quark mass is also studied as a function of the event kinematical properties in the lepton + jets decay channel. No indications of a kinematic bias are observed and the collision data are consistent with a range of predictions from current theoretical models of t (t) over bar production.
Keywords: STANDARD MODEL; TEVATRON; DECAY; BOSON